Presente simple - Cortés Fernández, Lidie Susana (Vida Científica Boletín Científico de la Escuela Preparatoria No. 4, 2013)
The present simple is one of the most useful and needed verb tenses in the English language learning. This tense allows the student to talk about activities that they usually do, as well as routines, likes and preferences.